#37: Diagnosis and Management of Vasa Previa. Issue 4 (December 2016) - Sinkey, R.G.; Odibo, A.O.; Dashe, J.S.
Abstract : ( Am J Obstet Gynecol 2015;213(5):615–619) Vasa previa is a condition that occurs in approximately 1 per 2500 deliveries when fetal blood vessels that are unprotected by the umbilical cord or placenta run through the amniotic membranes and pass across the cervix. Rupture of membranes causes these vessels to rupture, resulting in fetal hemorrhage, exsanguination, fetal asphyxia, or even death. Type I vasa previa occurs when a velamentous cord insertion between the umbilical cord and placenta is present, and fetal vessels that run freely within the amniotic membranes overlie the cervix. Type II vasa previa occurs when the placenta has a succenturiate lobe or is multilobed, and fetal vessels that connect the 2 placental lobes pass over or are near the cervix.